2017
DOI: 10.1111/jce.13325
|View full text |Cite
|
Sign up to set email alerts
|

Near‐field impedance accurately distinguishes among pericardial, intracavitary, and anterior mediastinal position

Abstract: Impedance values are significantly different among these three anatomical compartments. Therefore, impedance can be potentially used as a means to guide percutaneous epicardial access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The sensor provides visual feedback on pressure differences as the needle advances through different tissue layers. Burkland and associates 10 have introduced a similar device that relies on impedance feedback to determine the location of the needle.…”
Section: Discussionmentioning
confidence: 99%
“…The sensor provides visual feedback on pressure differences as the needle advances through different tissue layers. Burkland and associates 10 have introduced a similar device that relies on impedance feedback to determine the location of the needle.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, ICD implantation is performed based on conventional intraoperative criteria: the de brillation lead (DL) pacing threshold (PT) less than 1.0 V and VSA more than 5.0 mV [6]. Beyond technical aspects, several factors may in uence these measurements, including condition of the myocardial tissue surrounding the tip of the implanted lead [7][8][9]. In patients with prior myocardial infarction (MI) this may be due to scar or hibernated tissue with electrical heterogeneity in myocardium of the most frequently implanted positions, particularly an interventricular septum or apex.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with prior myocardial infarction (MI) this may be due to scar or hibernated tissue with electrical heterogeneity in myocardium of the most frequently implanted positions, particularly an interventricular septum or apex. Implantation of the DL into the area with myocardial scar may impair a proper functioning of DL, because the scar or hibernated myocardium has electrical heterogeneity and low signal amplitude [8,9]. This can lead to insu cient sensitivity of the intracardiac signal detection, pacing DL fails and as a result -an inappropriate ICD-therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond technical aspects, several factors may influence these measurements, including properties of the myocardial tissue surrounding the lead electrodes. 1,2 Prior studies suggested an association between temporal changes in some of these parameters and clinical events, such as heart failure functional class changes or cardiac arrhythmias occurrence. [3][4][5] However, it is unknown whether their values at implant could have a clinical relevance as a systematic analysis of association between baseline measurements and clinical outcomes has never been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond technical aspects, several factors may influence these measurements, including properties of the myocardial tissue surrounding the lead electrodes 1,2 . Prior studies suggested an association between temporal changes in some of these parameters and clinical events, such as heart failure functional class changes or cardiac arrhythmias occurrence 3–5 .…”
Section: Introductionmentioning
confidence: 99%